Zika –an Emerging Global Threat - Shakya, Priyanka; Sathian, Brijesh; Nayak, Niranjan (Nepal Journal of Epidemiology, 2016)
Zika virus disease (Zika) is a new emerging mosquito borne illness, transmitted by the bite of an infected mosquito especially Aedes aegypti. The infection, known as Zika fever often causes no or only mild symptoms which include fever, rash, joint pain, and conjunctivitis, which may last up to a week.